Language, literature and identity construction in pedagogical practices: Foreign language teaching in a resistance perspective - Luciana de Mesquita Silva; Alice Moraes Rego de Souza; Fabio Sampaio de Almeida (Arizona State University, 2018)
This paper aims to present and theorize "Sarau das Letras": languages in the construction of identities, an artistic and cultural activity carried out jointly by teachers and students of Spanish and English courses, which are offered within the scope of the Tourism undergraduate course at Cefet/RJ Petropolis. In terms of foundations, we intend to articulate the discursive perspective of language to postcolonial / decolonial theorization. Such theoretical articulations aim to bring up a certain conception of language as imbricated to the social context and as a space of manifestation and clashes between different discursive practices. The presentation of "Sarau" is made through a general description of the performances exhibited during the event and also through a more in-depth analysis of four poems recited by the students. By doing so, we try to show the importance of discussing and giving visibility to voices of resistance, which are sometimes subalternized. From the theoretical-practical reflection developed throughout this article, it was possible to understand the relevance of foreign language teaching in the critical and broad formation of citizens, considering the ethical and political commitment to our students, by sharing the view that, through language, positioning disputes about the diverse forms of being manifest themselves and circulate in our society.